Susceptibility of shallow foundation to rocking and sliding movements during seismic loading - Heron, Charles; Haigh, Stuart; Madabhushi, Gopal (Springer, 2014)
Current design codes prevent the rocking and sliding of shallow foundations during seismic loading despite much research indicating the beneficial nature of allowing such movements. The primary benefit is the partial isolation of the structure from the soil beneath and subsequently the reduced ductility demands on the superstructure, saving money and reducing the risk of collapse. However, further research is required in order to be able to fully model and predict the behaviour of the soil-foundation interface when sliding and rocking is permitted. The results presented in this chapter examine how several different parameters including structural stiffness, aspect ratio, soil relative density and earthquake magnitude affect the level of rotation and sliding experienced by the foundation. Six centrifuge tests were performed to examine how these parameters affected the response of the structure and high speed photography was used to track the movements of the foundation precisely. It was found that structures with a high centre of gravity slid more than structures with a low centre of gravity. Also, stiff structures were found to rotate more than flexible structures and structures located on dense sand rotate more than those located on loose sand.